Assessment of Strategic Development Opportunities of Regions for the Development of the Tourism Industry - Ahmad Ugli, Yorqulov Muhammadmurod (Indonesian Journal Publisher, 2025)
The tourism industry plays a vital role in the economic development of many regions around the world. As the demand for travel and leisure experiences grows, it becomes increasingly important to identify and assess the strategic development opportunities that regions can exploit to enhance their tourism industry. This paper aims to explore the potential strategies for developing regional tourism industries, taking into account both the challenges and opportunities present in the respective regions. Through a comprehensive literature review, analysis of regional data, and case studies, this paper assesses the factors that contribute to sustainable tourism development. The findings highlight key factors such as infrastructure, human resources, local culture, and natural resources, which serve as pillars for the successful development of tourism in regional settings.